How Important is the Timing of Radioiodine Ablation in Differentiated Thyroidal Carcinomas: A Referral Centre Experience - Simsek, F. S.; Balci, T. A.; Donder, Y.; Ugur, K.; Kilinc, F. (Elsevier Espana Slu, 2020)
Introduction: It's difficult to make a scientific, evidence-based approach about the timing of radioiodine remnant ablation (RRA) in patients with differentiated thyroid carcinomas (DTCs). Primary aim of the study was to reveal whether timing of RRA relates to achievement of non- structurally incomplete response (non-SIR) in low/intermediate and high-risk patients. Another aim was to reveal the correlation of timing with non-SIR status in reproductive-age women. Materials and Methods: Records of 279 low, intermediate, and high-risk patients were analysed, retrospectively. Number of days between surgery and RRA is referred to as timing. Low/intermediate-risk patients, high-risk patients, and low/intermediate-risk reproductive-age women were divided into non-SIR and SIR groups, according to 2015 American Thyroid Association guidelines for therapy response. The relationship between timing and therapy response was analysed statistically. Results: We could not find any significant relationship in patients with low/intermediate risk between timing and non-SIR, including women between 18-49 years of age (p >0.1). For high-risk patients, we found a statistically significant relationship between timing and non-SIR response. According to ROC analysis, RRA <= 58 days was found as a cut-off value. The sensitivity, specificity, positive likelihood ratio, and negative likelihood ratio were calculated as 83.3%, 70.0%, 2.78, and 0.24, respectively. Conclusion: RRA must be initiated within 58 days after surgery in patients with high-risk DTCs. Under this approach, risk of SIR and associated mortality risk may be reduced. RRA timing for women in reproductive ages with low/intermediate risk groups may be planned according to their pregnancy/breastfeeding intent. For other low/intermediate risk groups, they can safely proceed according to the capacity of the medical facility and related logistical considerations. (C) 2019 Sociedad Espanola de Medicina Nuclear e Imagen Molecular. Published by Elsevier Espana, S.L.U. All rights reserved.
Cómo es de importante el momento de la ablación con radioyodo en los carcinomas diferenciados de tiroides: la experiencia de un centro de referencia
Keywords: Time; Thyroid neoplasms; Iodine-131; Surgery